Determinación del efecto de la temperatura y empaque al vacío, en el tiempo de vida de anaquel del chocho salado y pasteurizado (lupinus mutabilis sweet), variedad Iniap 450 en “Corporación Casa producción y comercialización de productos alimenticios Corpocas”, parroquia Tanicuchí, barrio San Pedro. - Casa Tipán, Héctor Mauricio (2021)
The company Corporation house (CORPOCAS) carried out an investigation to improve the useful life of pasteurized lupine, vacuum packed with the use of a MULTIVAC R125 machine. Different tests were applied, in order to determine the best treatment and the longest useful life of the chocho. Physical-chemical, microbiological an sensory changes were analyzed, for this a completely randomized experimental design (DCA) was applied, with three factors: Factor A (pasteurized and unpasteurized chocho), Factor B (Temperature at 4 ° C and Room temperature at 25 ° C) and Factor C (vacuum packed and sheathed), applying two repetitions with a total of 16 treatments. The response variables that were studied in the InfoStat statistical program were: pH, humidity, total aerobic count, total coliforms, mildew and yeast and organoleptic tests; which were compared with the NTE INEN 2239: 2004 Standard. The determination of the useful life was performed based on the indirect accelerated method, which helped us to determine the estimated time of useful life in the second best treatments of each response variable. The data were taken on the first day, on the seventh day and on day 21, obtaining as best treatments: (pasteurized, vacuum packed, 4 ° C), with a pH of 6.55, mildew and yeasts <10 CFU / ml, (Pasteurized, vacuum packed, 25 ° C), pH 6.7, molds and levers <10 CFU / ml. Finally, the investigation was determined that pasteurization and packaging make influence the useful life of the food.